Assessment of Social Elements with Ecological Impact in the Historical Socio-Ecological Systems in the Jaltepeque Estuary Watershed - Magaña, Ariel Alexander Quintanilla (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2025)
The mangrove ecosystem-based management is not a simple task. It poses a challenge for nations, municipalities, and stakeholders that look to protect their livelihoods. The integration of watersheds provides a scope that includes freshwater and soil pollution in the upper basin. The Socio-ecological system framework offers a new vision for understanding how the social elements interact with the ecological cycles in an area without being limited by political boundaries. As well as the configuration of spatial patterns that discover indicators to establish action keys for ecosystems and livelihoods. However, understanding the present is insufficient to get the data needed to cover crucial thresholds impacting human beings and the ecological cycles in the mangrove forests and estuaries. Through a historical revision of 105 documents from the early 1900s to 2014, as well as 24 interviews were performed to delimit the configuration of two Socio-Ecological Systems in the Jaltepeque estuary watershed. First, which almost covers an 80-year period, has a primary factor: the no-limiting of cotton crops implies the replacement of the wetland area for more production. The second SES was started by the civil war in El Salvador and reconfigured to small subsistence production.